RESILIENCY OF WOMEN'S LAYOUT OF IMPACT OF THE COVID-19 PANDEMIC - Sinaga, Dameria; Simorangkir, Melda Rumia Rosmery (International Journal of Business, Law, and Education, 2023)
Reflecting on the implementation of physical distancing in Greater Jakarta since March 2021 due to the COVID-19 pandemic, Indonesia's economy grew 2.97% lower than the target of 4.4%. On the same occasion, he said that state budget revenue for the first quarter of 2020 still recorded growth of 7.7 percent or 16.8 percent. Meanwhile, absorption of state spending grew slightly by 0.1 percent to 17.8 percent in the first quarter of 2020. (Hanoatubun, 2020) During the COVID-19 pandemic, more than 1.5 million workers were laid off and laid off. This study aims to measure the resilience of women who have been laid off by the impact of the COVID-19 pandemic in carrying out their roles in the family. The method in this study uses a qualitative research method with a case study approach with purposive sampling. The results of this study found that the research subjects were able to overcome the pressure that occurred by being patient, enthusiastic, optimistic about the efforts made, and able to be grateful for the existing conditions. They can recover well and remain productive in carrying out their daily activities. Positive support from the closest people also plays a role in building the resilience of each subject.